The hidden danger: Silent celiac disease - Çaltepe, Gönül (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Çaltepe G. The hidden danger: Silent celiac disease. Turk J Gastroenterol 2018; 29: 530-1.